1999
DOI: 10.1002/(sici)1099-0992(199903/05)29:2/3<287::aid-ejsp928>3.0.co;2-5
|View full text |Cite
|
Sign up to set email alerts
|

The impact of context on gender social identities

Abstract: What follows is a quasi‐experimental study aiming to analyse the influence of the social division of roles (especially the division between public and private spheres of activity) on gender social identities. Subjects were asked to describe themselves as well as their images of the ‘perfect or ideal person’ in the context of their professional activities or their close relationships. The order of presentation (self‐description and the description of the ‘perfect person’) was balanced. We found that women and m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2000
2000
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(3 citation statements)
references
References 45 publications
0
2
0
1
Order By: Relevance
“…Because social identities emerge from identifications with self‐relevant groups and one's social position in terms of professional roles constitutes a central dimension of the self (Tajfel, 1978, 1982; Turner et al., 1987), an individual's occupational position can be a relevant source of internationalization of socially shared expectations in personality. Consistent with this, some studies have shown that identification with agentic and communal traits is influenced by one's professional status or occupation (Agronick & Duncan, 1998; Echebarria & Gonzalez, 1999; Kasen et al., 2006).…”
Section: Theoretical Background: the Relevance Of Agentic And Communa...mentioning
confidence: 73%
“…Because social identities emerge from identifications with self‐relevant groups and one's social position in terms of professional roles constitutes a central dimension of the self (Tajfel, 1978, 1982; Turner et al., 1987), an individual's occupational position can be a relevant source of internationalization of socially shared expectations in personality. Consistent with this, some studies have shown that identification with agentic and communal traits is influenced by one's professional status or occupation (Agronick & Duncan, 1998; Echebarria & Gonzalez, 1999; Kasen et al., 2006).…”
Section: Theoretical Background: the Relevance Of Agentic And Communa...mentioning
confidence: 73%
“…En este sentido podemos decir que nuestros datos corroboran la afirmación de Eagly y Mladinic (1994) relativa al aumento en la adscripción de rasgos masculinos en las mujeres de cara a su éxito profesional. En definitiva, la autopercepción de los sujetos cambia según los dominios y contextos en los cuales se desenvuelven, estando éstos a su vez íntimamente relacionados con los roles que los individuos desempeñan en su vida cotidiana (Spence, 1984;Ortiz y Valencia, 1998;Echebarría y González, 1999).…”
Section: Conclusionesunclassified
“…On the one hand, a functionalist social discourse legitimizes precarious jobs and blames women, resulting in an image of incompetence, laziness, and comfort ( Kelvin and Jarrett, 1985 ; Noguera, 2000 ). On the other hand, women perceive themselves according to traditional gender stereotypes ( Echebarria and González, 1999 ; Carter, 2014 ). This inequality, focused on training human capital ( Becker, 1962 ), is based on the gender stereotype of ‘the good woman’ ( Cornwall et al, 2008 ), who has to be efficient at work and in taking care of the family.…”
Section: Introductionmentioning
confidence: 99%